Examination of a herd experiencing Neospora caninum-associated abortion by a mouse monoclonal antibody-based competitive ELISA - Crisóstomo, João Afonso Coutinho (2024)
In the present study, a competitive enzyme-linked immunosorbent assay (cELISA), based on the 3.10.5 mouse monoclonal antibody, was developed to detect bovine antibodies to Neospora caninum. Sera from cattle infected with N. caninum, Besnoitia besnoiti, and Sarcocystis spp. were used to validate the test. The sera were also analysed by a p38-ELISA, Western blot, and immunofluorescence antibody test (IFAT). A Bayesian latent class analysis (BLCA) was performed using the Gibbs sampler to estimate the diagnostic characteristics of the cELISA. The results revealed a sensitivity of 98.5% (95% CI: 96.5% - 99.9%) and a specificity of 98.4% (95% CI: 97.1% - 99.4%). The cELISA was used to analyse cattle sera from a herd with suspected N. caninum-associated abortions and determine whether these abortions could be attributed to neosporosis. No definitive conclusions could be taken regarding the origin of the epidemic outbreak of abortion that occurred in the studied herd; - Análise de uma exploração com suspeita de abortos relacionados com infeção por Neospora caninumpor um ELISA de competição baseado emanticorposmonoclonaisde rato Resumo: No presente estudo foi desenvolvido um enzyme-linked immunosorbent assay (ELISA) de competição, baseado no anticorpo monoclonal de rato 3.10.5, para a deteção de anticorpos anti-Neospora caninum. Soros provenientes de animais infetados com N. caninum, Besnoitia besnoiti, e Sarcocystis spp. foram utilizados para a validação do teste. Estes soros foram testados por p38-ELISA, Western blot, e immunofluorescence antibody test (IFAT). Um modelo baseado em Estatística Bayesiana, usando o método de amostragem Gibbs, foi usado para estimar os parâmetros de diagnóstico do cELISA. A sensibilidade estimada foi de 98.5% (95% IC: 96.5% - 99.9%) e a especificidade de 98.4% (95% IC: 97.1% - 99.4%). O ELISA desenvolvido foi utilizado para analisar soros provenientes de uma exploração com suspeita de abortos relacionados com infeção por N. caninum, de forma a determinar se estes poderiam ser atribuídos a neosporose. A origem dos abortos epidémicos ocorridos na exploração em estudo não foi definitivamente determinada.